P190 Serum MMP-9: a novel biomarker for prediction of clinical relapse in patients with Quiescent Small Bowel Crohn's disease. (16th January 2018) - Yablecovitch, D; Kopylov, U; Lahat, A; Amitai, M M; Klang, E; Ben-Ami Shor, D; Neuman, S; Levhar, N; Fudim, E; Avidan, B; Selinger, L; Orbach, N; et al.
Abstract: Background: Predicting relapse in Crohn's disease (CD) patients may allow an early optimisation of treatment and possible reduction of subsequent complications. There is an increasing need for a novel and reliable non-invasive biomarkers for this purpose. Matrix metalloproteinase-9 (MMP-9) is a relatively new and promising marker of intestinal inflammation. We aimed to assess, for the first time, whether serum MMP-9 levels can predict clinical relapse in patients with quiescent small bowel CD. Methods: This was a post-hoc analysis of patients with quiescent small bowel CD who were included in a prospective observational study and followed until clinical relapse or the end of the 24 months study. Clinical relapse was defined as an increase in CD activity index (CDAI) score of at least 70 points from baseline, or an intensification of therapy, as per physician global assessment based decision. The patients were followed with serial magnetic resonance enterography (MREs) and capsule endoscopies (CEs). Small bowel inflammation was quantified by Lewis score (LS) for CE. Magnetic resonance index of activity (MaRIA) score was calculated for MRE. C-reactive protein (CRP) and faecal calprotectin (FC) were obtained at baseline and at each follow-up visit. Serum MMP-9 levels in baseline blood samples were quantified by enzyme linked immunoabsorbent assay and the correlation of MMP-9 levels with subsequent clinical flare was investigated. Results: Sixty-one patients were enrolled. After exclusion of three blood samples due to technical causes, there were 58 analysable samples from 58 CD patients (median age 29.5y, 43% female), of whom 16 have relapsed. Baseline MMP-9 was higher in patients who developed symptomatic relapse [median 661 ng/ml, 25–75 IQR (478.2–1441.3) vs. 525.5 ng/ml, (339–662.7), in relapsers vs. non-relapsers, respectively, p = 0.01]. ROC analysis of serum MMP-9 levels showed a fair discriminatory accuracy with an AUC of 0.72 (95% CI: 0.56–0.88). MMP-9 concentrations ≥945 ng/ml yielded the optimal cut-off in terms of combined sensitivity of 44% and specificity of 100% for detecting relapse. Exploratory analysis including only the 13 patients who had CDAI change>70 points demonstrated an improved discriminatory accuracy with AUC of 0.76 (95% CI: 0.58–0.93). MMP-9 concentrations displayed a moderate and low correlation with baseline FC and LS respectively (r = 0.46, p < 0.0001; r = 0.31, p < 0.05). No correlation was found between serum MMP-9 and CRP levels or MaRIA score. Conclusions: Serum MMP-9 may be a novel biomarker for prediction of relapse in CD patients with quiescent disease.